Adsorption and recovery of lithium ions from groundwater using date pits impregnated with cellulose nanocrystals and ionic liquid - Sara A. Wahib (17269246) (2022)
The study aims to prepare a novel low-cost and environmentally friendly adsorbent by using date pits (DP) impregnated with cellulose nanocrystals (CNCs) and ionic liquid (IL), named IL-CNC@DP. The batch adsorption of lithium onto IL-CNC@DP and DP were studied at different pH values, initial lithium concentrations, and temperatures. The thermodynamics constants of the adsorption process showed that the IL-CNC@DP was exothermic, did not favor a high level of disorder, and spontaneous in nature. At pH 6, there is a significant increase in the removal efficiency where it increased to 90%. This also could be explained by the fact that electrostatic attraction forces and hydrogen bonding existed between the protonated Li+ and the less protonated IL-CNC@DP adsorbent surface, which enhanced the percentage of Li+ removal. A strong inter- and intra-hydrogen bonding (O-H) stretching absorption is seen at 3311 cm−1 that occurs in cellulose components. In conclusion, the IL-CNC@DP in comparison to the DP confirmed exceptional results proving that the modification enhanced the remediation of the Li+ from water. Furthermore, the selectivity of IL-CNC@DP towards real groundwater samples isolated in Qatar depends upon the physicochemical characteristics of each element. Other Information Published in: Journal of Hazardous Materials License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jhazmat.2021.126657